"Naiset motkottaa aiheesta ja nalkuttaa syyttä". Kyselytesti verbien semanttisten sisältöjen arvioinnissa - Vanhatalo, Ulla (Virittäjä, 2002)
Using questionnaires to assess semantic content of verbs (englanti) 3/2002 (106) Using questionnaires to assess semanic content of verbs An ideal dictionary would also give the user plenty of detail on the meaning and usage of words that are near synonyms. Conventional dictionaries, however, are constrained by a strict alphabetical order and stringent limitations on space. Remarkably little attention has therefore been given to detailed lexical information or explanation. The study presented here investigates the use of questionnaire surveys to gather information on the implicit lexical knowledge of native speakers of a language. The words studied were 21 Finnish verbs expressing complaint, many of which can be classified as expressive (onomatopoeic-descriptive). In dictionaries, many of these verbs are presented as synonyms. The questionnaire respondents answered both standard and multiple-choice questions designed to test their understanding of the meaning and usage of the verbs. They were asked to assess the sex and age of the verb agent, the degree of anger, loudness of voice and extent of provocation. The study subjects comprised 154 native speakers of Finnish aged 16-18 years old. The results show that questionnaires can be used to obtain worthwhile information on the meaning and usage of particular words as implicitly understood by native speakers of the language. This type of information is not yet given in dictionaries. In specifying the sex of the agent, for example, as many as 97 per cent of respondents associated the verb nalkuttaa to nag with a female agent and 83 per cent associated the verb jurista to grumble with a male agent. The verbs nalkuttaa and motkottaa to carp are reported by dictionaries as being synonyms, but the study showed a clear difference between them in terms of e.g. loudness of voice, degree of anger and extent of provocation. In future, information based on tests of this kind could be used in dictionary definitions of words expressing feelings, other expressive words and many adjectives. The special advantage of the method is that it is empirical: it examines the understanding of the language by native speakers themselves. It can also take into account variations in lexical knowledge and usage. This type of information is particularly suited to presentation in hypertext format, since it is possible to simultaneously present a great deal of different information on each lexical entry. Ulla Vanhatalo Kielenainekset motkottaa (kieli: suomi, sivulla: 330) nalkuttaa (kieli: suomi, sivulla: 330)